Assessment of association of ACTN3 genetic polymorphism with Korean elite athletic performance - Hong, S. S.; Jin, H. J. (Genes & Genomics, 2013)
Genetic and environmental factors have long been suspected to influence on physical performance and athletic ability. Recent studies have suggested that the skeletal-muscle actin binding protein a-actinin-3 (ACTN3) gene was associated with athletic performance in Europeans. It would lead us to hypothesize that ACTN3 gene may be one of the factors that influence certain variation in muscle function, but origins and replicate tests remain to be elucidated. We analyzed ACTN3 genetic polymorphism to assess the possible role of the genotype differences (RR, RX, and XX) in elite athletic performance in a population-based case-control study in Korea. The ACTN3 gene locus was found to be no deviation from Hardy-Weinberg expectation. We observed a significant association between female sprint/power athletes (SPAs) and control (P=0.028), that of male SPAs or all SPA samples did not. The female SPAs appeared to have a dearth of 577 XX genotype (OR 0.104, 95 % CI 0.013-0.822, P = 0.011) compared with the control with a replicating finding in the Korean population. Thus, our results imply that the sex specific ACTN3R577X genotype may provide a significant effect on elite Korean female SPAs status, although larger sample sizes and functional studies are necessary to further elucidate these findings. Assessment of association of ACTN3 genetic polymorphism with Korean elite athletic performance.